2021
DOI: 10.3389/fgene.2021.699910
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of the Value of SMYD Family Members in the Prognosis and Immune Infiltration of Malignant Digestive System Tumors

Abstract: BackgroundThe SET and MYND domain-containing (SMYD) gene family comprises a set of genes encoding lysine methyltransferases. This study aimed to clarify the relationship between the expression levels of SMYD family members and the prognosis and immune infiltration of malignant tumors of the digestive system.MethodsThe Oncomine, Ualcan, Kaplan–Meier Plotter, cBioPortal, Metascape, and TIMER databases and tools were used to analyze the correlation of SMYD family mRNA expression, clinical stage, TP53 mutation sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…International Publisher infiltration of FoxP3+ regulatory T cells (Treg) in TME is a poor prognostic biomarker in HCC, but the densities of CD20+ B cells or CD57+ natural killer (NK) cells in HCC are positively related to the prognosis of HCC [8]. Furthermore, the correlation between genes that contribute to the prognosis of HCC and immune infiltration was investigated using transcriptomic data [9,10].…”
Section: Ivyspringmentioning
confidence: 99%
“…International Publisher infiltration of FoxP3+ regulatory T cells (Treg) in TME is a poor prognostic biomarker in HCC, but the densities of CD20+ B cells or CD57+ natural killer (NK) cells in HCC are positively related to the prognosis of HCC [8]. Furthermore, the correlation between genes that contribute to the prognosis of HCC and immune infiltration was investigated using transcriptomic data [9,10].…”
Section: Ivyspringmentioning
confidence: 99%
“…These proteins contain the SET domain, responsible for lysine methylation. The SET domain is divided into two segments by the MYND domain (Myeloid, Nervy, and DEAF-1), which is a unique characteristic of the SMYD family that facilitates protein-protein interactions [ 3 ]. While SMYD4 has been less studied in carcinogenesis compared to other members of the SMYD family, it has been identified as a potential tumor suppressor due to its observed downregulation in breast cancer [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…SMYD4 has been identified as a tumor suppressor gene in breast cancer [ 18 ], and SMYD5 may be involved in cancer and stem cell maintenance [ 19 , 20 ]. Finally, several studies have suggested the association of SMYDs with immune infiltration in breast cancer and digestive system malignancies [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%